Recent advances in antibacterial coatings for orthodontic appliances - Wang, Nannan; Yu, Jingjing; Yan, Jiarong; Hua, Fang (Frontiers in Bioengineering and Biotechnology, 2023)
In the process of orthodontic treatment, the presence of orthodontic appliances makes it difficult to clean tooth surfaces. This can lead to an increased level of bacterial colonization, resulting in enamel demineralization and periodontal diseases. Considering the large surface area that orthodontic appliances usually have and that they can be in direct contact with bacteria throughout the treatment, modifications in the form of coatings on the surface of orthodontic appliances can be an effective and practical approach to reducing bacterial proliferation and preventing relevant adverse effects. In this mini-review, we discuss various antibacterial coatings which have been applied onto orthodontic appliances in recent five years, as well as their antibacterial mechanisms and methods for the preparation of these coatings. From this mini-review, both orthodontists and researchers can get the latest findings in the field of antibacterial coatings onto orthodontic appliances, which is helpful for the decision-making in clinical practice and research activities.